2017
DOI: 10.1080/17474124.2018.1417034
|View full text |Cite
|
Sign up to set email alerts
|

Hepatorenal syndrome: the clinical impact of vasoactive therapy

Abstract: Hepatorenal syndrome (HRS) is a unique form of acute kidney injury seen in cirrhotic patients and associated with significant mortality and morbidity. Despite its impact, diagnosis and treatment of HRS remains challenging and this review aims to assess and compare the available vasoconstrictors used as first-line treatment for HRS. Areas covered: A literature review was undertaken on the use of vasoconstrictors in HRS, using PubMed/Medline database searches of: 'hepatorenal syndrome', 'HRS' and 'vasoconstricto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 66 publications
0
11
1
3
Order By: Relevance
“…Clinical guidelines recommend using vasoconstrictors in combination with albumin as the first-line treatment for HRS AKI 73 to counteract splanchnic arterial vasodilation. 74 The goal of using albumin is to combat the hemodynamic dysfunction by antagonizing the decreased effective circulating volume and increasing the mean arterial pressure.…”
Section: Vasoconstrictors and Albuminmentioning
confidence: 99%
“…Clinical guidelines recommend using vasoconstrictors in combination with albumin as the first-line treatment for HRS AKI 73 to counteract splanchnic arterial vasodilation. 74 The goal of using albumin is to combat the hemodynamic dysfunction by antagonizing the decreased effective circulating volume and increasing the mean arterial pressure.…”
Section: Vasoconstrictors and Albuminmentioning
confidence: 99%
“…Type 1 HRS was regarded as a rapidly progressing renal failure defined as the doubling of baseline sCr in less than 2 weeks to a value of greater than 2.5 mg/dl. 52 Type 2 HRS was seen as a less progressive renal failure with elevation of sCr to greater than 1.5 mg/dl. 52 More recently, the ICA has defined HRS as meeting the following criteria: i) presence of cirrhosis and ascites; ii) diagnosis of AKI in accordance with the ICA-AKI criteria; iii) absence of shock; iv) no improvement with 2 days of diuretic stoppage and plasma volume expansion with 1 g/kg body weight of albumin; v) absence of nephrotoxic drug use; vi) absence of macroscopic signs of structural renal disease (lack of proteinuria, haematuria, and abnormalities on renal ultrasonography).…”
Section: Variceal Bleedingmentioning
confidence: 99%
“…52 Type 2 HRS was seen as a less progressive renal failure with elevation of sCr to greater than 1.5 mg/dl. 52 More recently, the ICA has defined HRS as meeting the following criteria: i) presence of cirrhosis and ascites; ii) diagnosis of AKI in accordance with the ICA-AKI criteria; iii) absence of shock; iv) no improvement with 2 days of diuretic stoppage and plasma volume expansion with 1 g/kg body weight of albumin; v) absence of nephrotoxic drug use; vi) absence of macroscopic signs of structural renal disease (lack of proteinuria, haematuria, and abnormalities on renal ultrasonography). 50 Risk factors for the development of HRS include gastrointestinal bleeding, bacterial infection, spontaneous bacterial peritonitis, large-volume paracentesis, and alcoholic hepatitis.…”
Section: Variceal Bleedingmentioning
confidence: 99%
“…44,47,48 The combination of midodrine (an alpha-1 adrenergic agonist, dose of 5-15 mg orally every 8 hours 49,50 ) and octreotide (a somatostatin analog, dose of 100-200 µg of subcutaneous octreotide every 8 hours) is also considered an acceptable alternative for patients without central venous access receiving care on the medical floors, although this combination is not considered as effective as terlipressin. 51,52 While there are no generally accepted MAP goals for the treatment of HRS, a meta-analysis of 21 studies revealed that the magnitude of blood pressure elevation with vasopressors was more important than the specific type of vasopressor used. 53 Raising MAP by at least 10 to 15 mm Hg is necessary to see improvements in SCr.…”
Section: Clinical Management Of Hrsmentioning
confidence: 99%